Public Service Agency Policy and Effciency of Regional Airports in Indonesia - Rofii, Rofii; Soetjipto, Widyono (Fakultas Ekonomi dan Bisnis Universitas Lampung, 2025)
The Public Service Agency policy began to be implemented in Indonesia across hospitals, educational institutions, and airports following the enactment of Law No. 17/2003 on State Finance and Law No. 1/2004 on State Treasury. However, research examining BLU policy within the airport sector remains limited, with existing studies predominantly focusing on hospitals and educational institutions. This study aims to analyze the implementation process of the Public Service Agency policy at ten regional airports in Indonesia over the period 2016–2024 by examining the policy formulation, its application in airport operations, and airport performance using the Data Envelopment Analysis (DEA) and Tobit regression approaches. Based on the efficiency analysis using the Data Envelopment Analysis (DEA) approach, the Public Service Agency policy tends to be implemented at regional airports that are already efficient, although there is a tendency for airport performance to decline after the policy’s is implemented. According to the results of the Tobit Regression analysis, variables that significantly influence the efficiency scores of airports include the distance of the airport from the city center and regional GDP per capita. These findings provide an evaluative tool for assessing the performance of regional airports in Indonesia in implementing the BLU policy